Sosialisasi Pengenalan dan Implementasi Sistem Pembayaran Digital Menggunakan QRIS pada UMKM - Lestari, Desi Tika; Yanti Siburian, Crisya Damai; Ndraha, Ewisra (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to describe the process of socialization, introduction, and implementation of QRIS (Quick Response Code Indonesian Standard) in Micro, Small, and Medium Enterprises (MSMEs). QRIS is an electronic payment system that allows non-cash transactions using QR codes, which has been introduced by Bank Indonesia to improve efficiency and financial inclusion in Indonesia. This study was conducted using a qualitative approach and descriptive research methods. Data was collected through interviews with MSME owners, as well as through direct observation of QRIS implementation in several places. Data analysis was carried out using an inductive approach, by identifying themes and patterns that emerged from the collected data. The results of this study indicate that QRIS socialization to MSMEs is an important step to increase understanding and acceptance of this payment technology. Socialization was carried out through various methods, including counseling, training, and technical guidance organized by the research team. The introduction of QRIS among MSMEs also involved payment service providers, who provided the necessary technical and infrastructure support.